2019
DOI: 10.3390/w11091866
|View full text |Cite
|
Sign up to set email alerts
|

Water in Descriptions of Global Geoparks: Not Less Important than Geology?

Abstract: Water is an important landscape element of protected areas, but its significance to geoparks (parks representing geological heritage) is still unclear. The content of the official, standardized descriptions of the UNESCO global geoparks (144 in total) was analyzed in order to understand the consideration of water by geopark creators/managers. It was found that water objects (seas/oceans, rivers, and lakes are most common) are mentioned in 55% of these descriptions, and 47% of the latter bear photos of water ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…In order to consider aquatic diversity, we follow the classification as indicators considering the potential salutogenic effects of water access in different representations in Table 1 [ 12 , 13 , 19 , 115 , 116 , 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to consider aquatic diversity, we follow the classification as indicators considering the potential salutogenic effects of water access in different representations in Table 1 [ 12 , 13 , 19 , 115 , 116 , 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…The hydrological diversity is slightly lower in UGGs compared to areas outside. Ruban [ 78 ] analysed the official descriptions of 144 UGGs in order to understand the involvement of water by geopark creators/managers, and found that only 55% mention water, with 47% of those showing photographs of water objects, mainly to stress the aesthetic value. Our analyses suggests that the low hydrological diversity in UGGs can be explained by the overrepresentation of UGGs in mountains, as the hydrology in mountainous areas often consists of small and fragmented streams.…”
Section: Discussionmentioning
confidence: 99%
“…based on high-resolution LiDAR campaigns such as those from the GEDI mission [ 89 ], can also advance the quantification of geodiversity metrics at fine resolutions over a large spatial extent, for example by allowing better detection of first-order streams in mountains which are underrepresented in the currently available HydroSheds dataset [ 90 ]. Additional information on artificial dams, drainage and irrigation channels [ 77 , 91 , 92 ] or groundwater, springs, wetlands and other ‘water-related’ geofeatures could be relevant to include for capturing hydrological diversity globally and within UGGs [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cidade também conta com o desfile de Natal e com a tradicional Folia de Reis. Ruban (2019), a água é um elemento importante para a paisagem numa área de geoparque, este ressalta que as atividades turísticas nessas áreas podem levar à sua poluição. O município também explota o aquífero Emborê, principal aquífero do estado do Rio de Janeiro em termos de vazão e qualidade da água (Correia et al, 2016).…”
Section: Geofood Artesanatos E Festividadesunclassified